The Impact of a 24-h Ultra-Marathon on Salivary Antimicrobial Protein Responses - Gill, S. K.; Teixeira, A. M.; Rosado, F.; Hankey, J.; Wright, A.; Marczak, S.; Murray, A.; Costa, R. J. S. (International Journal of Sports Medicine, 2014)
Depressed oral respiratory mucosal immunity and increased incidence of upper respiratory symptoms are commonly reported after bouts of prolonged exercise. The current study observed the impact of a 24-h continuous overnight ultra-marathon competition (distance range: 122–208 km; ambient temperature range: 0–20°C) on salivary antimicrobial protein responses and incidence of upper respiratory symptoms. Body mass, unstimulated saliva and venous blood samples were taken from ultra-endurance runners (n=25) and controls (n=17), before and immediately after competition. Upper respiratory symptoms were assessed during and until 4-weeks after event completion. Samples were analyzed for salivary IgA, lysozyme, α-amylase and cortisol in addition to plasma osmolality. Decreased saliva flow rate (p<0.001), salivary IgA (p<0.001) and lysozyme (p=0.015) secretion rates, and increased salivary α-amylase secretion rate (p<0.001) and cortisol responses (p<0.001) were observed post-competition in runners, with no changes being observed in controls. No incidences of upper respiratory symptoms were reported by participants. A 24-h continuous overnight ultra-marathon resulted in the depression of some salivary antimicrobial protein responses, but no incidences of upper respiratory symptoms were evident during or following competition. Salivary antimicrobial protein synergism, effective management of non-infectious episodes, maintaining euhydration, and (or) favourable environmental influences could have accounted for the low prevalence of upper respiratory symptoms.
Keywords: immunoglobulin A; α-amylase; lysozyme; upper respiratory; running; water